Optimalisasi Model Pakem untuk Pengembangan Kemampuan Siswa yang Komprehensif pada Pembelajaran IPS (Studi Tindakan pada Kelas VI SDN 18 Mataram) - Dwi Istati Rahayu (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: National Competence-Based Curriculum and School Level Curriculum require that changes in the achievement of required basic competencies, the model of learning activities, and evaluation of learning patterns take place. This change is perceived differently by many teachers because of various reasons. This Classroom Action Research aims at developing students’ comprehensive abilities in accordance with the competencies required by optimizing the active, creative, effective and joyful learning model. This research was conducted in two cycles. The result shows that the implementation of the social studies by optimalizing the active, creative, effective and joyful learning model promotes both teachers’ and students’ level of enthusiasm, and students can develop their comprehensive abilities (cognitive, affective, and psychomotoric).